2009
DOI: 10.1152/ajpheart.00672.2009
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular function of isoproterenol-induced hypertrophied rat hearts perfused with blood: mechanical work and energetics

Abstract: Ϫ1 ⅐ day Ϫ1 for 3 days (Iso3) or 7 days (Iso7)]-induced hypertrophied rat heart preparation under isovolumic contractionrelaxation. We evaluated pressure-time curves per beat, end-systolic pressure-volume and end-diastolic pressure-volume relations, and myocardial O 2 consumption per beat (V O2)-systolic pressure-volume area (PVA; a total mechanical energy per beat) linear relations at 240 beats/min, because Iso-induced hypertrophied hearts failed to completely relax at 300 beats/min. The LV relaxation rate at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 36 publications
1
14
0
5
Order By: Relevance
“…The Western blot analysis revealed that the expression of TRPC1 was upregulated in the CH group, while the levels of TRPC3, TRPC6 and NCX1 remained stationary. The data were consistent with previous reports [10,21], and were shown in Fig. 1.…”
Section: Resultssupporting
confidence: 93%
“…The Western blot analysis revealed that the expression of TRPC1 was upregulated in the CH group, while the levels of TRPC3, TRPC6 and NCX1 remained stationary. The data were consistent with previous reports [10,21], and were shown in Fig. 1.…”
Section: Resultssupporting
confidence: 93%
“…Considered with the present experiments, these data imply a role for sympathetic dysregulation in the progression of cardiac disease in diabetic rats. Continuous β-adrenergic stimulation by infusion of isoproterenol generates cardiac hypertrophy, bradycardia, and slowed end-diastolic relaxation rates [43]. NET knockout mice display elevated cardiac NE, hypertension and tachycardia [44].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our evidence suggests that for the perfused heart as much as one-third of the ATP production is required to maintain viability of cardiomyocytes, even when not contributing to contractile work. When normalised ( moles metabolism/unit RPP) palmitate oxidation is tightly coupled to cardiac work, and for the current protocol this most likely represents the decline in ATP synthesis as a consequence of decreased O 2 delivery limiting the work done by the heart [40]. This suggests close coupling of oxidative phosphorylation, and a high degree of mitochondrial efficiency.…”
Section: Cardiac Metabolismmentioning
confidence: 93%